Proceedings of the Sixth Symposium on Usable Privacy and Security 2010
DOI: 10.1145/1837110.1837122
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of structural network clustering for group-based privacy control in social networks

Abstract: Users of social networking sites often want to manage the sharing of information and content with different groups of people based on their differing relationships. However, grouping contacts places a significant configuration burden on the user. Automated approaches to grouping may have the potential to reduce this burden, however, their use remains largely untested.We investigate people's rationales when grouping their contacts for the purpose of controlling their privacy, finding six criteria that they comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
75
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 16 publications
2
75
1
1
Order By: Relevance
“…Early work exploring group creation focused primarily on privacy control interfaces [14,16]. In this domain, manual creation and annotation of groups was costly in terms of time and frustration due to unintuitive interfaces.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Early work exploring group creation focused primarily on privacy control interfaces [14,16]. In this domain, manual creation and annotation of groups was costly in terms of time and frustration due to unintuitive interfaces.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies on group creation demonstrate that people are not willing to use current grouping techniques in OSNs as they were intended. For example, a study on Facebook lists at 2010 showed that only 20% of participants' friends were included in Facebook lists and none of the participants used these lists for controlling privacy [14]. In a related study, Kelly et al asserted that participants using Facebook lists to create groups included few friends [16].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations